Atomic Layer Deposited Gallium Oxide Buffer Layer Enables 1.2 V Open‐Circuit Voltage in Cuprous Oxide Solar Cells. (23rd May 2014) - Lee, Yun Seog; Chua, Danny; Brandt, Riley E.; Siah, Sin Cheng; Li, Jian V.; Mailoa, Jonathan P.; Lee, Sang Woon; Gordon, Roy G.; Buonassisi, Tonio
<x xml:space="preserve">Abstract</x> The power conversion efficiency of solar cells based on copper (I) oxide (Cu2O) is enhanced by atomic layer deposition of a thin gallium oxide (Ga2O3) layer. By improving band‐alignment and passivating interface defects, the device exhibits an open‐circuit voltage of 1.20 V and an efficiency of 3.97%, showing potential of over 7% efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>